Job satisfaction of academic staffs at a higher educational institution: A case study of UiTM, campus Sungai Petani - Ju, Soon Yew; Din, Mohd Salleh; Kong, Lai Kuan (2004)
The purpose of this study was to examine the academic staffs’ job satisfaction in a higher educational institution, namely UiTM (Universiti Teknologi MARA), campus Sungai Petani. Survey was conducted using instrument Job Descriptive Index (JDI) and few demographic variables to measure the academic staffs job satisfaction. The findings shown that majority of the academic staffs were highly satisfied with three aspects of job, which are job in general, present job, and present pay. About half of them indicated highly satisfied with co-workers and supervision. Conversely, only a small portion of them highly satisfied with the opportunities for promotion. The result of this study shown that in general, academic staffs were highly satisfied with their job, except the opportunities for promotion. In this aspect, in order to motivate them, top management should reviewed the promotional system in the organization based on academic merit and contribution where the academic staffs that have excellent job performance will be rewarded and promoted accordingly. The promotional structure, system and process should be clearly communicated and understood by all the academic staffs.